Differential pulse polarographic determination of enalapril maleate - Elmali, F; Alpdogan, G; Aycan, S; Sungur, S (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY, 2003)
A differential pulse polarographic (DPP) method has been developed for the quantitative analysis of enalapril maleate. Enalapril maleate gives a peak at -1.4 V in methanol. A calibration curve was constructed for the 20 -100 mug ml(-1) concentration range. As a reference method, a reversed phase high performance liquid chromatographic procedure has been developed. Commercially available tablets were analysed by the two methods. Statistical evaluations indicated that there was no significant difference between the mean values and precisions of the two methods at a 95% confidence level.
Keywords: differential pulse polarography; high performance liquid chromatography; enalapril maleate; tablets; SPECTROPHOTOMETRIC DETERMINATION; CAPILLARY-ELECTROPHORESIS; LIQUID-CHROMATOGRAPHY; HYDROCHLOROTHIAZIDE; FORMULATIONS; HPLC; Chemistry; Engineering